PENGEMBANGAN MODUL KOMPUTER AKUNTANSI BERBASIS PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA KELAS XI AKUNTANSI - Fitriani, Devita Eka; ., Jaryanto; Zoraifi, Renata (FKIP Universitas Sebelas Maret, 2017)
ABSTRACTThe objective of this research is to investigate the feasibility and effectiveness of scientific ap-proach-based computer accounting module to improve learning independence of the students in Grade XI of Accounting. This research used the Research and Development method referring to the develop-ment procedure claimed by Borg and Gall (1989). The developed module was validated by a learning material expert, a learning media expert, and practitioners. The subjects of the initial experiment con-sisted of 12 students, while the subjects of the field experiment consisted of 30 students in Grade XI of Accounting 1 as the experimental class and 30 students in Grade XI of Accounting 2 as the control class. The data of the research were collected through observation sheet, interview sheet, and questionnaire. They were qualitatively and quantitatively analyzed by using the Miles and Hubermanâs model of analy-sis and the statistical descriptive and inferential model of analysis through t-test respectively. The results of the research are as follows: Firstly, the developed model is feasible to be used as indicated by the av-erage scores of 82.97% by the experts and 80.37% by the students. Secondly, the developed model is ef-fective to improve the studentsâ learning independence as indicated by the results of the analysis with the paired samples t-test where the p-value is 0.000<0.05 and the independent samples t-test where the p-value is 0.000<0.05. The percentages of score on the learning independence of the experimental class and the control class are 82.67 and 73.69 respectively. Thus, the developed scientific approach-based computer accounting module is feasible and effective to improve learning independence of the students in Grade XI of Accounting.Keywords: Module, Computer Accounting, Scientific Approach, Learning Independence.ABSTRAKPenelitian ini bertujuan untuk mengetahui kelayakan dan keefektifan modul komputer akuntansi berbasis pendekatan saintifik untuk meningkatkan kemandirian belajar siswa kelas XI Akuntansi. Penelitian ini merupakan penelitian pengembangan (Research and Development) yang mengacu pada prosedur pengembangan Borg dan Gall (1989). Modul yang dikembangkan telah divalidasi oleh ahli ma-teri, ahli media dan praktisi. Subjek uji coba awal terdiri dari 12 siswa. Subjek uji coba lapangan terdiri dari 30 siswa kelas XI AK1 sebagai kelas tindakan dan 30 siswa kelas XI AK2 sebagai kelas kontrol. Instrumen pengumpulan data menggunakan lembar observasi, lembar wawancara, dan angket. Teknik analisis data menggunakan analisis kualitatif model Miles dan Huberman (1992), dan analisis kuantitatif menggunakan statistik deskriptif dan inferensial melalui uji-T. Hasil penelitian menunjukkan bahwa per-tama, modul sangat layak digunakan berdasarkan penilaian ahli dengan skor rata-rata 82,97% dan re-spon siswa sebesar 80,37%. Kedua, modul efektif untuk meningkatkan kemandirian belajar. Hal ini dibuktikan dari hasil analisis paired samples t-test dengan signifikansi 0,000<0,05 dan independent sam-ples t-test dengan signifikansi 0,000<0,05. Hasil persentase skor kemandirian belajar kelas tindakan adalah 82,67 dan kelas kontrol 73,69. Dengan demikian, pengembangan modul komputer akuntansi ber-basis pendekatan saintifik layak dan efektif untuk meningkatkan kemandirian belajar siswa kelas XI Akuntansi.Kata Kunci: Modul, Komputer Akuntansi, Pendekatan Saintifik, Kemandirian Belajar.